Current Status and Associated Factors of Depression and Anxiety Among the Chinese Residents During the Period of Low Transmission of COVID-19 - Shen, Xin; Yan, Shijiao; Cao, Hui; Feng, Jing; Lei, Zihui; Zhang, Weixin; Lv, Chuanzhu; Gan, Yong (Frontiers in Psychology, 2021)
Background: The outbreak of coronavirus disease 2019 (COVID-19) has contributed to depression and anxiety among the general population in China. The purpose of this study is to investigate the prevalence and associated factors of these psychological problems among Chinese adults during the period of low transmission, which could reflect the long-term depression and anxiety of the COVID-19 outbreak. Methods: A cross-sectional survey was conducted in China from 4 to 26 February 2021. Convenient sampling strategy was adopted to recruit participators. Participants were asked to filled out the questions that assessed questionnaire on the residents' depression and anxiety . Results: A total of 2,361 residents filled out the questionnaire. The mean age was 29.72 years (SD=6.94) and majority of respondents were female (60.10%). Among the respondents, 421 (17.83%), 1470 (62.26%), and 470 (19.91%) were from eastern, central, and western China, respectively. 1704 (72.17%) consented COVID-19 information has been disclosed timely. 142 (6.01%) and 130 (5.51%) patients suffered from depression and anxiety symptoms. Furthermore, some influencing factors were found, including marital status, place of residence, employment status. Conclusion: This study revealed that anxiety and depression still are potential depression and anxiety for some residents, which suggested early recognition and initiation of interventions during the period of low transmission is still indispensable.